2021
DOI: 10.3389/fmed.2020.586390
|View full text |Cite
|
Sign up to set email alerts
|

Independent Risk Factors for Deaths due to AIDS in Chongqing, China: Does Age Matter?

Abstract: Background: People living with HIV (PLWH) are aging worldwide, and different management strategies may be required for older and younger PLWH. However, demographic characteristics, illness distribution, mortality, and independent risk factors in the PLWH population in China are not yet fully understood, especially in patients aged 50 years or older.Methods: We conducted a retrospective analysis of 4445 HIV-positive Chinese inpatients in Chongqing, China.Results: The mortality rate in patients 50 years or older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Unlike earlier studies [ 9 , 26 , 27 ], interval between ATT to ART was not associated with the later development of paradoxical TB-IRIS in the current study, this may be due to the relatively uniform schedule for 2 week in the time from ATT to ART. Late diagnosis is extremely severe among hospitalized PLHIV in Chongqing, it’s reported that the prevalence of advanced HIV was as high as 77.4% [ 19 ], and those usually combined with multiple pathogenic bacteria infection and multiple organ system damages, especially CNS infections, so the complicated circumstances led to a delay in the initiation of ART to approximately 2 weeks or more, however, the overall prognosis was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike earlier studies [ 9 , 26 , 27 ], interval between ATT to ART was not associated with the later development of paradoxical TB-IRIS in the current study, this may be due to the relatively uniform schedule for 2 week in the time from ATT to ART. Late diagnosis is extremely severe among hospitalized PLHIV in Chongqing, it’s reported that the prevalence of advanced HIV was as high as 77.4% [ 19 ], and those usually combined with multiple pathogenic bacteria infection and multiple organ system damages, especially CNS infections, so the complicated circumstances led to a delay in the initiation of ART to approximately 2 weeks or more, however, the overall prognosis was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, previous studies on the effectiveness of B/F/TAF have not specifically analyzed patients with baseline HIV RNA >500,000 copies/mL. In Chongqing, China, where the prevalence of advanced HIV among hospitalized patients living with HIV exceeds 70%, [2] up to 25% of patients have baseline HIV-1 RNA >500,000 copies/mL in our study, and many patients have opportunistic infections. In such a complex medical setting, the virological suppression rates of patients using B/F/TAF remain uncertain.…”
mentioning
confidence: 84%
“…Talaromycosis is an independent predictor of death in PLWHA in hospital, especially in older patients [4].…”
Section: Introductionmentioning
confidence: 98%